Security And Development Of Modern Computer Networks: A Literature Review On Monitoring, Cyber Threats, And Intelligent Detection Systems - Dela Susanti; Dina Miftahul Jannah; Amsar Yunan; Depi Ginting; Fera Anugreni (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2025)
The development of modern computer networks has become a fundamental foundation for the implementation of various digital services in the era of digital transformation. Improvements in network speed, scalability, and integration provide significant benefits for the education, government, industrial, and financial sectors. However, behind these advancements, serious challenges emerge in terms of network security. The increasing complexity of modern network architectures raises the potential for cyber threats that may compromise data confidentiality, integrity, and availability. This study aims to examine the development and security of modern computer networks using a descriptive qualitative approach through a literature review method. Data sources were obtained from scientific articles, academic books, and relevant publications discussing computer networks, network monitoring, cyber threats, and intelligent attack detection systems. The results indicate that cyber threats such as phishing, malware, port scanning, and Distributed Denial of Service (DDoS) remain dominant issues. Network monitoring plays an important role as an early detection mechanism, but it has limitations in handling complex and dynamic attacks. Therefore, the implementation of machine learning-based intrusion detection systems is considered capable of enhancing network security effectiveness. The integration of technology, monitoring systems, and improved user security awareness is a key strategy in building adaptive and sustainable network security systems.